2013
DOI: 10.1016/j.acap.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Use of Active Ingredient Information for Low Socioeconomic Status Parents' Decision-Making Regarding Cough and Cold Medications: Role of Health Literacy

Abstract: OBJECTIVE Parent administration of multiple medications with overlapping active ingredients places children at risk for overdose. We sought to examine how parents use active ingredient information as part of the process of selecting a cough/cold medication for their child, and how health literacy plays a role. METHODS Experimental study of parents of children presenting for care in an urban public hospital pediatric clinic. Parents were asked to determine which of 3 cough/cold medications could be given to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Having a child with fever requires caregivers to assess a numeric value and recognize and adequately treat symptoms. Adults with low health literacy have poor understanding of illness 8,19,20 and are known to dose antipyretic medications incorrectly, 9,10 leading to poor treatment of fever at home. Lack of health system navigational skills and hesitance to seek information about illness, could lead to higher ED use.…”
Section: Discussionmentioning
confidence: 99%
“…Having a child with fever requires caregivers to assess a numeric value and recognize and adequately treat symptoms. Adults with low health literacy have poor understanding of illness 8,19,20 and are known to dose antipyretic medications incorrectly, 9,10 leading to poor treatment of fever at home. Lack of health system navigational skills and hesitance to seek information about illness, could lead to higher ED use.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the parents with low health literacy harder understand the importance of vaccination and are not completely able to realize the risks of malnutrition and overweight. They can hardly recognize hazards in the home, which leads to frequent injuries of children 4,[5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, low health literacy among the parents cause difficulties to dose the medicine which is purchased without a prescription (OTC) for a child. Errors in dosing the OTC medicines to children can cause the risk of adverse effects and therapeutic failure 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…The NVS has shown predictive ability in a study of emergency department utilization whereas the S-TOFHLA did not. Others have found the NVS to distinguish health outcomes in patients, including diabetes, 15 obesity, 16 health system navigation, 17 medication dosing and understanding, 18,19 and use of mHealth, 20 Additionally, the NVS has been used to assess health literacy in adolescents. 15,21,22 As in our study, another study found that the NVS performed superiorly in detecting a relationship between limited health literacy and a health outcome (knowledge of appropriate antibiotic use) whereas the S-TOFHLA did not.…”
Section: Discussionmentioning
confidence: 99%